Migrants and Firms: Evidence from China - Clement Imbert; Marlon Seror; Yifan Zhang; Yanos Zylberberg (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper estimates the causal effect of rural-urban migration on urban production in China. We use longitudinal data on manufacturing firms between 2001 and 2006 and exploit exogenous variation in rural-urban migration due to agricultural price shocks. Following a migrant inflow, labor costs decline and employment expands. Labor productivity decreases sharply and remains low in the medium run. A quantitative framework suggests that destinations become too labor-abundant and migration mostly benefits low- productivity firms within locations. As migrants select into high-productivity destinations, migration however strongly contributes to the equalization of factor productivity across locations.
Keywords: D24; J23; J61; O15; 330; rural-urban migration; structural transformation; urban production